The occurrence of pressure ulcers and psychophysical efficiency in patients with cognitive disorders provided with long-term institutional care in Poland. - Kuźmicz, Ilona; Brzostek, Tomasz; Górkiewicz, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background: Number of people requiring long-term institutional care is increasing in Poland. Older age, cognitive impairment, multidisease, falls, pressure ulcers, deficits in psychophysical efficiency often occur in patients benefiting from this type of service. Aim of the study: The aim of the research was to evaluate the association between pressure ulcers and psychophysical efficiency in patients with cognitive disorders provided long-term institutional care. Material and method: Study involved 160 persons with cognitive disorders (125 women and 35 men), age between 61–100 years.  The study group included 80 patients of long-term care institution and 80 inhabitants of the social welfare home. The standardized Cognitive Assessment Scale (CAS), the Barthel scale,  the Edmonton Functional Assessment Tool (EFAT) and the Observational Anxiety and Depression Scale were used as the research tools. The assessment was repeated three times: at the beginning, after three and six months. Results and conclusion: Respondents who experienced pressure ulcers (N = 28, 17.5%) were characterized by more severely impaired cognitive function (p <0.001); dysfunction of functional status (p <0.001), higher symptoms of tension, and anxiety (p = 0.02) and a lower physical mobility (p <0.001) than other patients without pressure ulcers. Patients with cognitive disorders provided with a long-term stationary care need systematic assessment of psychophysical activity, as a part of the of the pressure ulcer prevention program.